Outlook for the economic development of Northern regions of Asian Russia - Olga Aleshina (European Regional Science Association (ERSA), 2010)
Northern territories in Asian Part of Russia hold significant mineral resource abundance. This region can also be viewed as an outstanding geopolitical and military potential of Russia. On the other hand, economic development here is embarrassed with severe climatic conditions, underpopulation and unavailability of infrastructure. Targeting to proportion costs and benefits of the rising economic activity on the territory we analyze its prospects and challenges. For the central point would be taken intricacies with transport component when running projects of the local deposits deployment. As non-ferrous metals are the most likely to form the essential branch of Northern industry, they will originate substantial material flow in the area. This leads us to the point local transportation lines should be improved by far. Sea carriage is almost exclusive mode of transportation available for the purposes of Arctic littoral regions and furthermore the list expensive. Therefore reinforcement of Northern Sea Route (NSR) plays the vital role in developing of in question regions' economy. Multisectoral multi-regional model allows to link growth of non-ferrous metals complex and progress of sea transport corridor (NSR). Suppose the whole country is oriented for the maximization of public welfare and economic growth rate. In these terms our investigation led to a key-note conclusion: long-term goals of the whole country are attained superior when running active economical policy in the North. The crux is large non-ferrous metals sector companies are ready to enter the area if the government provides substantial financial support for infrastructure improvements. Simultaneously, in our case economic development should not implicate people to settle the territory. Rotation system is implied. All potential resource abundant zones are to be attached to the congruent NSR harbors, thereby regional centers. The system of aqua-territorial industrial complexes is suggested as an efficient form of economic life in Northern regions of Asian Russia.
Keywords: 330; Arctic zone; natural resources potential; geopolitical potential; transport accessibility; Northern Sea route (NSR); aqua-territorial production (industrial) complexes